Hatchery Strain Contributions to Emerging Wild Lake Trout Populations in Lake Huron. (19th June 2018) - Scribner, Kim; Tsehaye, Iyob; Brenden, Travis; Stott, Wendylee; Kanefsky, Jeannette; Bence, James
Abstract: Recent assessments indicate the emergence of naturally produced lake trout ( Salvelinus namaycush ) recruitment throughout Lake Huron in the North American Laurentian Great Lakes (>50% of fish <7 years). Because naturally produced fish derived from different stocked hatchery strains are unmarked, managers cannot distinguish strains contributing to natural recruitment. We used 15 microsatellite loci to identify strains of naturally produced lake trout ( N = 1567) collected in assessment fisheries during early (2002–2004) and late (2009–2012) sampling periods. Individuals from 13 American and Canadian hatchery strains ( N = 1143) were genotyped to develop standardized baseline information. Strain contributions were estimated using a Bayesian inferential approach. Deviance information criteria were used to compare models evaluating strain contributions at different spatial and temporal scales. The best performing models were the most complex models, suggesting that hatchery strain contributions to naturally produced lake trout varied spatially among management districts and temporally between time periods. Contributions of Seneca strain lake trout were consistently high across most management districts, with contributions increasing from early to late time periods (estimates ranged from 52% to 94% for the late period across 8 of 9 districts). Strain contributions deviated from expectations based on historical stocking levels, indicating strains differed with respect to survival, reproductive success, and/or dispersal. Knowledge of recruitment levels of strains stocked in different management districts, and how strain-specific recruitment varies temporally, spatially, and as a function of local or regional stocking is important to prioritize strains for future stocking and management of the transition process from primarily hatchery to naturally produced stocks.